1986
DOI: 10.1038/icb.1986.40
|View full text |Cite
|
Sign up to set email alerts
|

Relative Levels of Thecal Blood Flow in Atretic and Non‐atretic Ovarian Follicles of the Conscious Sheep

Abstract: Summary. The relative level of blood flow through thecal capillaries (RTF) in individual atretic and non-atretic follicles >1 mm was measured in conscious ewes by injecting 15 nm radioactive microspheres into the aorta near the origin of the ovarian artery, and determining the ratio of radioactivity per mg protein in theca of individual follicles to that in the nonluteal portion (stroma plus follicles < 1 mm diameter) of the corresponding ovary.In follicles > 1 mm diameter, RTF in those showing advanced stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The amount of capillary blood flow to both ovulatory and atretic antral follicles in sheep has been vastly studied using radiolabeled microspheres in anaesthetized and conscious sheep, with inconsistent findings. Some studies suggested that capillary blood flow did not differ between atretic and non-atretic follicles of the same size and was not related to their steroidogenic activity (Bruce and Moor, 1976), whereas others indicate that blood supply to follicular theca cells in antral follicles showing advanced stages of atresia was significantly less compared with that in healthy follicles (Carson et al, 1986). Our results indicate that high-velocity blood flow is actually the "two-faced" marker of antral follicular health and oocyte competence.…”
Section: Groupmentioning
confidence: 52%
“…The amount of capillary blood flow to both ovulatory and atretic antral follicles in sheep has been vastly studied using radiolabeled microspheres in anaesthetized and conscious sheep, with inconsistent findings. Some studies suggested that capillary blood flow did not differ between atretic and non-atretic follicles of the same size and was not related to their steroidogenic activity (Bruce and Moor, 1976), whereas others indicate that blood supply to follicular theca cells in antral follicles showing advanced stages of atresia was significantly less compared with that in healthy follicles (Carson et al, 1986). Our results indicate that high-velocity blood flow is actually the "two-faced" marker of antral follicular health and oocyte competence.…”
Section: Groupmentioning
confidence: 52%
“…Changes in the microvasculature prelude the formation of the interstitial gland of the ovary, and thecal capillary angiogenic processes support a gradual increase of ovarian blood¯ow during follicle growth (Macchiarelli et al, 1993). On the other hand, reduced thecal blood¯ow is associated with advanced atresia of antral follicles (Carson et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In the ewe, it has been shown that the inner capillary wreath of atretic follicles was about one-third as vascular and contained 85% fewer erythrocytes than did non-atretic follicles (Hay et al, 1976). The level of capillary blood flow within the theca of follicles in advanced stages of atresia was significantly less than that in non-atretic follicles (Findlay & Carson, 1980;Carson et al, 1986). Although alterations in blood flow were not detected in early atresia, another study has shown degenerative changes in the inner capillary network of the theca of primary atretic sheep fol¬ licles (O'Shea et al, 1978).…”
Section: Autoradiographymentioning
confidence: 98%